The Effect of Cigarette Smoking Duration on Hemoglobin Level Measured with Cyanmethemoglobin Method - Fitriani Kahar; Ririh Jatmi Wikandari; Irnawati Irnawati; Martha Silpa Penmaley (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2022)
In Indonesia, cigarette consumption is quite prevalent and has been become more common over time. According to Riskesdas (Baseline Health Research from Agency of Health Research and Development) study in 2018, the national percentage of people aged who smoke increased from 2016-2018, namely from 3.39% in 2016, 3.9% in 2017 and 9.65% in 2018. Smoking habits will negatively affect human health. Cigarette smoke contains various of different chemicals that are harmful to health, including nicotine addiction, tar (carcinogen or cancer-causing), and carbon monoxide. When inhaled, they form carboxyhemoglobin with Hb (Hemoglobin). When this occurs, the amount of Hb available for oxygen transport is reduced. By way of compensation, the body will produce more red blood cells. The objective of the study was to determine the hemoglobin levels in smokers with smoking durations of 3 years, 4 years and 5 years. This study is quasi-experimental. Determine hemoglobin readings using a photometer 5010 with the Cyanmethemoglobin method. Up to 20 samples were analyzed with SPSS version 20 with Anova analysis at 95% confidence level. The results of statistical analysis showed p-value <0.05, which means that there is a significant effect between variables and vice versa. Hb level comparison between durations of smoking are of 3 years with an average value of 14.8, Hb levels of 4 years with an average value of 14.53, and Hb levels of 5 years with an average value 15.94. The results showed that there was an effect of smoking duration on the results of the examination of hemoglobin levels in smokers of 3,4 and 5 years with the greatest effect being smokers with a duration of 5 years. The duration of smoking impact on hemoglobin levels.